Analysis of plant galactolipids by reversed-phase high-performance liquid chromatography/mass spectrometry with accurate mass measurement - Zábranská, Marie; Vrkoslav, Vladimír; Sobotníková, Jana; Cvačka, Josef (Chemistry and physics of lipids, 2012)
The composition of plant membrane lipids was investigated by reversed-phase high performance liquid chromatography mass spectrometry with accurate mass measurement. The data dependent methods for the analysis of monogalactosyldiacylglycerols (MGDGs) and digalactosyldiacylglycerols (DGDGs) have been developed. The optimised chromatographic systems were based on a 2.0 mm i.d. Nucleosil C18 column with methanol/water (MGDGs) or acetonitrile/methanol/water (DGDGs) gradients. The galactolipids were ionised by electrospray operated in the positive ion mode and identified based on their MS/MS spectra. High resolution spectra with accurate masses were found to be essential for correct interpretation of the MS data. The elution order of non-oxidised MGDGs and DGDGs followed the equivalent carbon numbers. The methods were applied for detailed characterisation of the MGDGs and DGDGs in the leaves of Arabidopsis thaliana and Melissa officinalis.
Keywords: meduňka; Chromatography, High Pressure Liquid; Oxidation-Reduction; oxidace-redukce; Arabidopsis; hmotnostní spektrometrie s elektrosprejovou ionizací; Melissa; Spectrometry, Mass, Electrospray Ionization; Chromatography, Reverse-Phase; Galactolipids; vysokoúčinná kapalinová chromatografie; chromatografie s reverzní fází; galaktolipidy